Social networking services : a new platform for participation in government programmes and policies among Nigerian youths - Ezema, Ifeanyi J. (2021)
Background. Many youths have adopted social networking media for communication with friends, family members and the general public. Objective. This study examined the participation of youths in government programmes and policies in Nigeria using social networking media. Method. A total of 200 Nigerian youths were sampled from four Nigerian universities. A structured questionnaire was administered to the respondents and 190 (95%) were properly completed. Results. The major social networking media used by Nigerian youths are Facebook, Google+, 2go, Skype and Twitter. They are mainly used for “social interaction,” “study, teaching and learning,” “information dissemination” and “research and academic purposes.” The youths rarely use these sites to participate in governance. The major challenges faced in the use of social networking are a lack of control on the activities of the users, power failures, the high cost of accessing the Internet, and poor Internet connectivity. Nigerian youths employ social networking to aggregate their views in government policies such as environmental issues, health, power supply, education, human capital development and security issues. The youths believe that social networking has improved participatory democracy in education and human capital development, health, environmental issues, power supply and budget monitoring. Conclusion. Social networking has dramatically improved the participation of youths in national discourses. The results of the study can serve as a useful guide on the use of social networking services for participatory democracy by youths in developing countries.